ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PERILAKU PENGELOLAAN KEUANGAN (Studi Kasus Pada Mahasiswa Fakultas Ekonomika Dan Bisnis Universitas Wijayakusuma Purwokerto) - Isnaeni Rokhayati; Harsuti Harsuti; Sodik Dwi Purnomo; Carla Selvianandia Alam (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of this study was to determine and analyze financial literacy, financial attitudes, locus of control, and peers on financial management behavior in students of the Faculty of Economics and Business, Wijayakusuma University, Purwokerto. The research method uses multiple linear regression analysis. The population in this study were students of the Faculty of Economics and Business, Wijayakusuma University, Purwokerto, who opened 1,599 respondents with a sample of 100 respondents. The sampling technique used proportional random sampling. The results of the study prove that financial literacy, financial attitudes, locus of control and peers have a positive and significant effect on financial management behavior in students of the Faculty of Economics and Business, Wijayakusuma University, Purwokerto. This finding implies that students can improve financial literacy, financial attitudes, locus of control and peers to be better, so that the level of financial management behavior they have will also increase and in making financial decisions will be better. Future research is expected to add independent variables such as spiritual intelligence, financial experience, social status of parents and increase in population as well as expansion of research.